Measurement of exhaled nitric oxide in man. - Borland, C. (1993)
BACKGROUND--Nitric oxide is released from pulmonary endothelial cells and contributes to the low pulmonary vascular resistance. The resistance pulmonary arteries are in close anatomical proximity to membranous airways, so it is likely that some pulmonary endothelial nitric oxide will enter the airspace to allow its measurement in the exhaled breath. METHODS--Exhaled air was collected from a single full exhalation and during tidal breathing. This was analysed for concentrations of nitric oxide, nitrogen dioxide, and carbon dioxide to give alveolar (FA) and mixed expired (FE) concentrations. Eight normal subjects were studied and laboratory air was similarly analysed using, respectively, chemiluminescent and infrared analysers. RESULTS--There was no relation between FA concentrations and the laboratory air concentrations. From the single breath, the ratio of (Fano/Faco2) x (Feco2/Feno) had a mean value of 0.92 (95% confidence interval 0.7 to 1.14). As this does not differ from unity, nitric oxide is likely to be derived from the same regions of the lungs as carbon dioxide. During tidal breathing the Feno ranged from 8.3 to 20.3 parts per billion. CONCLUSIONS--It is possible to measure endogenous pulmonary nitric oxide production in the exhaled air in man.